NEED ANALYSIS OF ESP FOR NON-ENGLISH STUDY PROGRAM - Rini Ekayati; Imelda Darmayanti Manurung; Elvita Yenni (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
In non-English study programs, English learning material is arranged based on the specificities of the English learners themselves, commonly known as English for Specific Purpose (ESP). By using a qualitative approach and descriptive method, this study aims to map the students’ English language skills, determine the objectives of learning English, and the concept of ESP material needed by students in the non-English Study Program at  UMSU. Sources of data in this study were 80 (eighty) respondents (students) from non-English study programs who had already completed their general English course. Data analysis was performed by using qualitative descriptive methods in terms of numbers and percentages. The results show that the students’ needs vary from one student to another depending on their respective fields of knowledge. The students’ average ability starts from the low until intermediate level, and speaking and listening skills cover those needed by the learners of the respective study program. Their learning objectives are divided into two criteria, short-term goals related to current needs such as academic/educational needs and long-term goals related to their world of work after completing education. The concept of ESP English learning needed depends on the varying needs of each existing non-English study program. Thus, the ESP concept that is designed must be adapted to these needs.